(untitled) (Docentes 2.0 Journal, 2019)
Higher education has been considered in the last years worldwide as the bus for the improvement and complementation of the life of the human being, being able to be a fundamental base for sustainable development, as described by the Organization of the unit nations through its strategic objective 2020/2030 number 4. In addition to promoting access to it inclusive, equitable, promoting values and innovative solutions to the problems of societies from the latest advances in technology. In Venezuela, historically there are many problems that have been dragging in the higher education sector and this has lately been accentuated by the economic crisis of these years which has removed many teachers and students from their classrooms.